Manifestations of Cytomegalovirus Infection - Price, Patricia; Makwana, Nandini; Brunt, Samantha (IntechOpen, 2013)
Cytomegalovirus (CMV) is carried by 50 100% of the worlds population throughout their lives. Consequences are most readily seen in immunocompromised individuals such as organ transplant recipients, HIV-infected patients and new born infants. This book gives an in-depth view of manifestations of CMV infection in immunocompromised individuals: how it affects the immune system and how it is diagnosed and treated. The book also sheds light on the epidemiology and impact of CMV in sub-Saharan Africa, and also associations with age related disease that are more commonly seen in the western world. It particularly details a recent discovery between CMV and tumour immuno-biology. The book explores the development of a few compounds and also highlights the need to discover novel antiviral agents in future.